2010
DOI: 10.1097/aln.0b013e3181dfd31b
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Intrathecal Administration of the Quaternary Lidocaine Derivative, QX-314, Produces Irritation and Death in Mice

Abstract: Lumbar intrathecal QX-314 concentration-dependently produced irritation and death in mice, at lower concentrations than those associated with robust motor blockade. Although QX-314 did produce long-lasting neural blockade, these findings indicate that QX-314 is unlikely to be a suitable candidate for spinal anesthesia in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…7 This may explain why intrathecal lidocaine does not produce the sustained severe acute irritation associated with QX-314. 29 That said, lidocaine is well known to be neurotoxic, and on the basis of the current study, it would seem possible that Ca 2ϩ influx mediated by TRPV1 activation [53][54][55] contributes to LA-induced cell death by inducing necrotic and apoptotic mechanisms. 56,57 The cellular degeneration caused by QX-314 chloride (60 mM) and bromide (Ն30 mM) in this study may well relate to the adverse intrathecal effects observed in vivo.…”
Section: Pain Medicinementioning
confidence: 99%
See 3 more Smart Citations
“…7 This may explain why intrathecal lidocaine does not produce the sustained severe acute irritation associated with QX-314. 29 That said, lidocaine is well known to be neurotoxic, and on the basis of the current study, it would seem possible that Ca 2ϩ influx mediated by TRPV1 activation [53][54][55] contributes to LA-induced cell death by inducing necrotic and apoptotic mechanisms. 56,57 The cellular degeneration caused by QX-314 chloride (60 mM) and bromide (Ն30 mM) in this study may well relate to the adverse intrathecal effects observed in vivo.…”
Section: Pain Medicinementioning
confidence: 99%
“…29 In general, pain upon injection of LAs is a wellknown phenomenon and often a source of discomfort for patients undergoing local anesthesia. 49 One possible mechanism may be the low pH of some LA formulations, 50 because TRPV1 is considered the main transducing receptor system for proton-induced excitation of nociceptive sensory neurons.…”
Section: Pain Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…However, activating membrane channels such as the TRV1 channel has been reported to allow QX314 entry into the neurons and to block the Na v channel from the interior and result in a selective block of the TRPV1 expressing primary afferent [150]. Intrathecal QX316 has been reported to produce significant pain behavior after intrathecal delivery in rodent models and this may reflect upon its ability to concurrently activate the TRPV1 channel [151]. It should be noted that while this section considers the role of sodium channel blockage in reducing axon excitability, it has been shown that conditions leading to an enhanced expression of sodium channels often lead to a reduction in the expression of potassium channels which further contributes to membrane excitability [152].…”
Section: Future Directions For Spinal Sodium Channel Blockersmentioning
confidence: 99%